1971
DOI: 10.2134/agronj1971.00021962006300020028x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Effects of Nitrogen Fertilizer on the Development and Downward Movement of Soil Acidity in Relation to Level of Fertilization and Crop Removal in a Continuous Corn Cropping System1

Abstract: The effect of NH4NO3 in a continuous corn cropping system on the depth distribution and amount of soil acidity produced was studied on four medium‐acid, prairie‐derived soils. To avoid the confounding effect of soluble salts, pH determinations were made after preliminary leaching of the soils and also by the 0.01 M CaC12 method. The amounts of acidity were measured by determining the quantities of CaCO3 required to bring the N‐treated plots to the pH of the No‐N plots. With amounts of N ranging from 1,525 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 15 publications
1
15
1
2
Order By: Relevance
“…4). Thus the amount of acidity entering and remaining in the soil from ammoniacal N sources depends largely on the relative magnitudes of these two processes (Pierre et al, 1971). One mole of H + ions are consumed per mole of NO 3 reduced to N 2.…”
Section: Denitrificationmentioning
confidence: 99%
“…4). Thus the amount of acidity entering and remaining in the soil from ammoniacal N sources depends largely on the relative magnitudes of these two processes (Pierre et al, 1971). One mole of H + ions are consumed per mole of NO 3 reduced to N 2.…”
Section: Denitrificationmentioning
confidence: 99%
“…In general, N fertilizers affect soil acidity because of the preferential uptake of nitrate-N to bases by most crops and the excretion of hydroxide ions to balance the charge reduces acidity (Jolley & Pierre 1977, Pierre et al 1971. Juo et al (1995aJuo et al ( , 1995bJuo et al ( , 1996 reported soil acidification followed by a considerable decline of exchangeable Ca in the topsoil horizons of the Egbeda series under continuous maize-based systems, which would arise from nutrient removal by crop harvest (Jaiyeoba 1995, Sharma et al 2009), application of ammoniacal fertilizers and nitrification of applied N (Stumpe & Vlek 1991).…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Analysis of variance confirmed that this soil-pH change could be attributed to liming (Table 3). Since soil acidity penetrates soil very slowly (18), the most intense acidity would be expected to be on or near the soil surface. Due to the very rapid increase in pH within the 0-5 cm interval, surface liming appears to have corrected the intense surface acidity within two months.…”
Section: Soil-ph Response In Surface Five CMmentioning
confidence: 99%
“…Timely broadcasts of limestone onto the soil surface will raise surface soil-pH to acceptible levels and will maintain these levels despite annual applications of ammonium fertilizers (4). If high rates of fertilizers are applied onto continuous corn without accompanying lime applications, surface acidity can become severe and acidity may penetrate deeper than five cm (18).…”
Section: Introductionmentioning
confidence: 99%